Causes and consequences of liana infestation in southern Amazonia. (27th August 2020) - Reis, Simone Matias; Marimon, Beatriz Schwantes; Morandi, Paulo S.; Elias, Fernando; Esquivel‐Muelbert, Adriane; Marimon Junior, Ben Hur; Fauset, Sophie; de Oliveira, Edmar Almeida; van der Heijden, Geertje M. F.; Galbraith, David; Feldpausch, Ted R.; Phillips, Oliver L.
Abstract: Lianas, a key component of tropical forests, can limit growth of trees, impacting both the structure and functioning of forests, and are expected to benefit from fragmentation and potentially from global climatic changes. While it is critical to understand the impacts of liana infestation on contemporary tropical forests across large geographical areas, to date most liana studies have been focussed on single or few sites. We measured and quantified liana infestation of 16, 066 trees with diameter ≥10 cm in 27 plots distributed across southern Amazonia, a region characterized by substantial ecological and environmental variation and environmental change. We examined the influence of potential drivers of liana infestation at the plot, species and individual tree level. Additionally, we evaluated the effect of liana infestation on tree growth. More than half of all trees had lianas in their crown. At the plot level, infestation by lianas was driven by forest structure but not by the studied climate or soil fertility variables, though low levels of liana infestation were found in seasonally flooded forests. At the tree level, larger and stouter trees had a greater proportion of their crown infested with lianas. At the species level, trees belonging to intrinsically slow‐growing, dense‐wooded species were more susceptible to liana infestation. Liana infestation had a negative impact on tree growth, with growth of heavily infested trees reduced by 33% compared to non‐infested. The impact of liana infestation on tree growth was strongest for the best‐lit tree crowns, indicating that lianas act to reduce the large competitive advantage that well‐lit trees otherwise hold over their neighbours. Synthesis . Lianas are a pervasive and influential feature of the extensive forests at the southern edge of Amazonia. The degree of liana infestation in forests was closely linked to species‐level variables such as potential growth and wood density as well as the size of the individual tree. The growth of heavily infested trees was particularly restricted by lianas, and especially so for trees growing in otherwise favourable conditions, indicating the potential for lianas not only to reduce forest growth rates overall, but also to modify competitive hierarchies among trees within tropical forests. Abstract : Lianas are a pervasive and influential feature of the extensive forests at the southern edge of Amazonia. Our long‐term research here shows that liana infestation is closely linked to tree properties, including species‐level variables such as potential growth and wood density as well as the dimensions of individual trees. The growth of heavily infested trees is strongly restricted by lianas, especially for trees growing in otherwise favourable conditions. Overall, lianas not only reduce forest growth rates but may also modify competitive hierarchies among trees in tropical forests. (Photo credits: Ben Hur Marimon Junior). Editor's Choice Resumo: Lianas, um componente essencial das florestas tropicais, podem limitar o crescimento das árvores, impactando a estrutura e o funcionamento das florestas, e é esperado que se beneficiem da fragmentação de habitats e mudanças climáticas globais. Embora seja essencial entender os impactos da infestação por lianas nas florestas tropicais contemporâneas em grandes áreas geográficas, até o momento a maioria dos estudos são realizados em um ou poucos sítios. Medimos e quantificamos a infestação por lianas em 16.066 árvores com diâmetro ≥10 cm em 27 parcelas distribuídas na borda sul da Amazônia, uma região caracterizada por ampla variação ecológica e ambiental e mudanças climáticas. Examinamos os possíveis fatores determinantes da infestação por lianas ao nível de parcela, espécie e de indivíduo. Além disso, avaliamos o efeito da infestação por lianas no crescimento das árvores. Mais da metade das árvores estavam com a copa infestada por lianas. Ao nível da parcela, a infestação por lianas foi relacionada com a estrutura da floresta, mas não com as variáveis de clima ou fertilidade do solo avaliadas, embora baixos níveis de infestação por lianas tenham sido encontrados nas florestas sazonalmente inundadas. Ao nível de indivíduo, as árvores maiores e mais robustas (menos esbeltas) tiveram uma proporção maior de suas copas infestadas por lianas. Ao nível de espécie, árvores pertencentes a espécies com crescimento intrinsecamente lento e de madeira densa foram mais suscetíveis à infestação por lianas. A infestação por lianas teve um impacto negativo no crescimento das árvores, com o crescimento de árvores fortemente infestadas reduzido em 33% em comparação com as não infestadas. O impacto da infestação por lianas no crescimento das árvores foi mais evidente para as árvores que possuíam a copa mais iluminada, indicando que as lianas podem reduzir a grande vantagem competitiva que essas árvores mantêm sobre as árvores vizinhas. Síntese . Lianas são uma característica generalizada e influente nas florestas na extensa borda sul da Amazônia. O grau de infestação por lianas em florestas foi intimamente ligado a variáveis ao nível de espécie, tais como crescimento potencial e densidade da madeira, além do tamanho de cada árvore. O crescimento de árvores fortemente infestadas foi particularmente restringido por lianas, especialmente para as árvores que crescem em condições favoráveis, indicando o potencial das lianas não apenas para reduzir as taxas de crescimento da floresta em geral, mas também para modificar hierarquias competitivas entre as árvores nas florestas tropicais.